Planting geometry and seed tuber size effects on potato (Solanum tuberosum) productivity - KUMAR, VIVEK; AULAKH, C S; KAUR, JASHANJOT (The Indian Journal of Agricultural Sciences, 2021)
The experiment was conducted during rabi 2014-15 and 2015-16 at Punjab Agricultural University, Ludhiana (India) to optimize planting geometry (50 cm × 15 cm, 65 cm × 11.5 cm, 70 cm × 10.7 cm and 75 cm × 10 cm) and seed tuber size (25-35 mm, 35-45 mm, 45-55 mm) for higher seed-grade and total tuber yield of potato (Solanum tuberosum L.). Planting geometry didn't significantly influence the growth and productivity of potato. However, the effect of seed tuber size was significant as large (45-55 mm) and medium (35-45 mm) sized tubers produced higher yield (8.3 and 7.4 t/ha, respectively) of small sized (45 mm) (20.2 t/ha) was obtained with small sized seed tubers. The highest net returns (â‚¹ 381.11 thousand/ha) were obtained with medium sized seed tubers as compared to small and large sized seed tubers. Therefore, medium sized seed tubers (35-45 mm) should be used for higher seed-grade and total potato tuber yield as well as better economic returns, irrespective of the planting geometry, under Punjab conditions.